Dental Age, Agenesis, and Morphology in Patients With Operated Single-Suture Craniosynostoses. (March 2021) - Leinonen, Sami; Rice, David; Leikola, Junnu; Heliövaara, Arja
Objective: The aim of this study was to evaluate the dental age, agenesis, and morphology of children with surgically operated single-suture craniosynostoses from orthopantomographs. Design: A single-centered cross-sectional observational archival study. Patients: A sample of 196 Finnish patients with single-suture craniosynostosis without additional birth defects or syndromes (excluding Muenke syndrome) was included in this study. Main Outcome Measures: Dental age was assessed using the method developed by Demirjian et al. and modified by Nyström et al. for the Finnish population. Methods described by Tulensalo et al. and Oehlers et al. were used to study taurodontism and dens invaginatus, respectively. Results: The study sample of 149 patients was divided into 3 groups: patients with sagittal synostosis (n = 103), coronal synostosis (n = 25), and metopic synostosis (n = 21). Orthopantomographs taken on average at ages 8.20 to 8.33 were used. The dental ages in different groups were on average 0.37, 0.60, and 0.66 years ahead of normative values, for sagittal, coronal, and metopic groups, respectively. Tooth agenesis, taurodontism, and invaginated teeth were found in all groups with invaginations having a high prevalence. Peg-shaped upper lateral incisors and one geminated lower lateral incisor were also found. Conclusions: These descriptive data may help improve dental care in patients with single-suture craniosynostosis.